Las armas nucleares y el carácter de las relaciones internacionales - Walker, Ignacio (Estudios Internacionales, 1986)
This paper aims to provide some elements to answer the following question: Have nuclear weapons changed the character of international relations? We hypothesize that nuclear weapons have significantly affected the character of international relations. One of the fundamental assumptions of this essay is that countries are at least trying to survive. To support this hypothesis, tentative propositions are elaborated, namely: Nuclear weapons have made the destruction of all humanity objectively feasible for the first time in history; Nuclear weapons have changed the character of war; Limited nuclear war is unthinkable; Nuclear deterrence can no longer be relied upon, and; Nuclear weapons have affected the system of nation states. Through these it is intended to argue that nuclear weapons have significantly affected the character of international relations.